2017
DOI: 10.4209/aaqr.2016.10.0440
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Automated System (PPWD/PILS) for Studying PM2.5 Water-Soluble Ions and Precursor Gases: Field Measurements in Two Cities, Taiwan

Abstract: An automated system consisting of a particle-into-liquid sampler (PILS) and a parallel plate wet denuder (PPWD) coupled with an ion chromatography was used for simultaneous measurement of ambient water-soluble ions in PM 2.5 and precursor gases. The performance of the PPWD/PILS was validated by comparing it with the PDS (porous metal denuder sampler) for precursor gases (NH 3 , HONO, HNO 3 and SO 2 ) and PM 2.5 ionic species (NH 4 + , NO 3 -, SO 4 2-, Na + , Cl -and K + ) measured in Taipei and Hsinchu Cities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The field comparison results of the PPWD-PILS-IC with the PDS for some major WSI species (Na + , K + , NH 4 + , Cl − , NO 3 − , and SO 4 2− ) are shown in Figure 4. It is found that the linear regression slopes and coefficient (R 2 ) of the determination range from 0.99 to 1.17 and from 0.88 to 0.98, respectively, which are better than those (slope 0.75-0.97 and R 2 0.77-0.94) in Li et al [31]. For K + , Na + , and NH 4 + , the improvement is even more obvious with higher R 2 of 0.89, 0.92, and 0.93, respectively (R 2 = 0.77, 0.77, and 0.89, respectively in the previous study) implying good stability of the monitoring system and the manual sampler.…”
Section: Isorropia-ii Thermodynamic Equilibrium Modelmentioning
confidence: 72%
See 3 more Smart Citations
“…The field comparison results of the PPWD-PILS-IC with the PDS for some major WSI species (Na + , K + , NH 4 + , Cl − , NO 3 − , and SO 4 2− ) are shown in Figure 4. It is found that the linear regression slopes and coefficient (R 2 ) of the determination range from 0.99 to 1.17 and from 0.88 to 0.98, respectively, which are better than those (slope 0.75-0.97 and R 2 0.77-0.94) in Li et al [31]. For K + , Na + , and NH 4 + , the improvement is even more obvious with higher R 2 of 0.89, 0.92, and 0.93, respectively (R 2 = 0.77, 0.77, and 0.89, respectively in the previous study) implying good stability of the monitoring system and the manual sampler.…”
Section: Isorropia-ii Thermodynamic Equilibrium Modelmentioning
confidence: 72%
“…In comparison, the PPWD/PILS consisting of PPWD [36,37] and PILS [38,39] and coupled with the IC (i.e., PPWD-PILS-IC) developed by our group [31] showed good agreement with the PDS for precursor gases (slope 0.92-.04) and PM 2.5 ion species as well (slope 0.75-0.97 and R 2 : 0.77-0.94). In addition, the PPWD-PILS-IC system has low MDLs (method detection limit) which are less than 0.01 µg/m 3 for Na + , Ca 2+ , NO 2 − , and SO 4 2− and 0.02 µg/m 3 for NH 4 + , NO 3 − , and Cl − , respectively.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The average concentration of chemical components showed that local air pollution also influenced air quality in Kumamoto. For simultaneous measurement of ambient water-soluble ions in PM 2.5 and precursor gases, Li et al (2017) developed an automated system consisting of a particle-into-liquid sampler (PILS) and a parallel plate wet denuder (PPWD) coupled with an ion chromatography. The performance of the PPWD/PILS was validated by comparing it with the PDS (porous metal denuder sampler) and the accuracy of the system for precursor gases was found to outperform the other commercial systems.…”
mentioning
confidence: 99%